Problematik Interpretasi Pengaturan Kepailitan Terhadap Jabatan Notaris di Indonesia - Amanda Maylaksita (Lex Renaissance, 2019)
Bankruptcy regulation according to Article 12 point a of Law No. 2 of 2014 on Notary Positions lead to different interpretations and this article provide sanctions to Notaries by dismissing them disrespectfully if the Notaries has been declared bankrupt by a court decision. This disrespectful dismissal is a treatment that is not in accordance with the concept of bankruptcy that has been regulated in Law No. 37 of 2004 on Bankruptcy. This study aims to determine and analyze bankruptcy regulation for Notaries based on Law No. 2 of 2014 on Notary Positions and Law No. 37 of 2004 on Bankruptcy as well as the legal consequences of Notaries declared bankrupt. This is a type of normative legal research using the legislation and conceptual approach and analyze it using descriptive qualitative methods. This research uses primary and secondary legal materials. The results of this study conclude that the regulation of bankruptcy of a Notary Public based on Article 12 point a of the Notary Law is not to cause disrespectful dismissal from his position. Notary as a legal subject that represents an individual who has a debt. The legal consequences of a bankrupt notary based on the Bankruptcy Law only causes a person to lose the right to act freely on his assets but not lose the right to carry out his profession and position. Suggestions from this research are, the government needs to do a review in order to amend the regulation on bankruptcy for the Notary to avoid mis-interpretations.